EFEKTIVITAS PENGGUNAAN TEKNIK ROLE PLAYING UNTUK MENINGKATKAN PERILAKU ASSERTIF PADA SISWA KORBAN BULLYING DI SMP NEGERI 4 PALOPO - Tabang, Nur Intan Syahputri; Septya Suarja; Andi Nurhayati; Nur saqinah Galugu (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to determine the effectiveness of role playing techniques in improving assertive behavior among students who are victims of bullying at SMP Negeri 4 Palopo. This research uses a quantitative approach with a pre-experimental design of the one-group pretest-posttest type. The subjects of the study were 10 students who were identified as bullying victims, selected using purposive sampling based on interviews and observations conducted with the school counselor (BK teacher). The main instrument used in this study was a Likert-scale questionnaire on assertive behavior, supported by observation sheets and interview guidelines as complementary data. Prior to its use, the questionnaire was tested for validity and reliability. The validity test was conducted using Pearson correlation on 30 trial students, resulting in 41 valid items with r-count values greater than the r-table (0.361). The reliability test showed a Cronbach’s Alpha value of 0.874, indicating high internal consistency. Data analysis techniques included descriptive analysis, Shapiro-Wilk normality test, and hypothesis testing using the paired sample t-test. The results showed a significant increase in posttest scores compared to pretest scores, with a significance value of 0.000 (p < 0.05). These findings indicate that the role playing technique is effective in enhancing assertive behavior in students who are victims of bullying. The implication of this study suggests that school counselors should consider applying this technique as an intervention strategy to build students’ confidence and assertive communication skills in school settings